Two new species of Notosacantha Chevrolat, 1834 from India (Coleoptera: Cassidinae: Notosacanthini) - Sekerka, Luká (Zootaxa, 2008)
Notosacantha cherrapunjiensis and N. dembickyi, new to science, are described and figured from Meghalaya state, NE India.